Community Roles tokoh Perempuan pada Era Perang Dunia II dalam Anime Kono Sekai no Katasumi ni karya Sunao Katabuchi - Narayan, Ni Putu Padma Krishna; Luhur Wedayanti, Ni Putu; Widya Purnawati, Ketut (Humanis; Vol 25 No 4 (2021), 2021)
This study aims to know how Community Roles that are played by the women during World War II, in the anime entitled Kono Sekai no Katasumi ni by Sunao Katabuchi. The analysis was done by using the Gender Analysis Frameworks by Caroline Moser (1993). The data were collected by watching the anime and applied the note taking technique. The qualitative analysis of the data shows that women character in the anime was very active in their community. They join the organization namely  Dai Nippon Fujinkai and all the activities in their neigbourhood. Those activities show their community roles.